2020
DOI: 10.1108/rsr-03-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Belief in importance of information literacy abilities among undergraduates. Underlying factors and analysis of variance

Abstract: Purpose The purpose of this paper is to analyse the levels of belief in importance of information literacy abilities (BILAs) among an undergraduates’ sample. The aim is, on the one hand, to discover if there is a representative latent structure and, on the other hand, to know the existing differences according to external variables such as academic degree, course, gender and age. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…We also used the validated instrument of Pinto ( 2010 ), a simplified version of Information Literacy Humanities Social Sciences (IL-HUMASS), for perception of information literacy. IL-HUMASS has been used in a number of studies (Pinto, 2010 ; Pinto et al, 2019 , 2020 , 2021 ). This instrument allowed us to explore the perceptions of pre-service teachers about the phenomenon of information literacy.…”
Section: Methodsmentioning
confidence: 99%
“…We also used the validated instrument of Pinto ( 2010 ), a simplified version of Information Literacy Humanities Social Sciences (IL-HUMASS), for perception of information literacy. IL-HUMASS has been used in a number of studies (Pinto, 2010 ; Pinto et al, 2019 , 2020 , 2021 ). This instrument allowed us to explore the perceptions of pre-service teachers about the phenomenon of information literacy.…”
Section: Methodsmentioning
confidence: 99%
“…Another major limitation is that the gender distribution among participants is uneven (43 females and 17 males). Despite the fact that this females/males disparity has been evidenced in other studies that involve university students (Dolni car and Boh Podgornik, 2023;Pinto et al, 2020), we should acknowledge that this is a serious shortcoming that may lead to biased results. Additionally, data were collected from two specific academic tasks rather than a full repertoire of diverse tasks.…”
Section: Methodological Limitationsmentioning
confidence: 75%
“…To start, it is important to clarify that the term “contextual factors” is one of various designations used to refer to “factors which reflect a particular context, characteristics unique to a particular group, community, society and individual” (Barzilai-Nahon et al , 2010, p. 644). Others include demographic characteristics (Creswell and Creswell, 2018), demographic parameters (Dolničar and Boh Podgornik, 2023), demographic variables (Aharony and Gazit, 2019), contextual variables (Pinto et al , 2020), social variables (Valverde-Crespo et al , 2022) and socio‐demographic information (Wang et al , 2023). Age and gender are perhaps the most common contextual factors examined in educational research (Cohen et al , 2018; Creswell, 2015).…”
Section: Rationale Of the Contextual Factors Examined In The Present ...mentioning
confidence: 99%
“…12 Pinto et al analyzed Spanish university students' beliefs in the importance of IL skills and found mixed results; of particular concern were that specific skills favored by instructional librarians, such as using a library catalog, using databases, and knowing information search strategies, were rated relatively low by these students. 13 Gross and Latham found that university students did not see the value of IL and hence IL instruction, nor did they view IL as a distinct skill set. 14 Kim and Shumaker found that students who take a course that includes a significant IL assignment rate their IL instruction and their own IL skills higher than those students without an IL assignment.…”
Section: Literature Reviewmentioning
confidence: 99%